DX243 counteracts both acoustic trauma-induced reduction in cortical brain oscillations and cochlear synaptopathy - Fink, Stefan; Harasztosi, Csaba; Xie, Li; Silvente, Stephane; Attali, Pierre; Caron, Nicolas; Singer, Wibke; Rüttiger, Lukas; Knipper, Marlies (Frontiers in Pharmacology, 2026)
BackgroundWith age, even mild acoustic injuries can accumulate - ultimately leading to a characteristic clinical picture of age-related hearing loss with the risk of cognitive decline. Age-related hearing loss is currently attributed to the loss of a most vulnerable auditory fiber type contributing to hearing in background noise. Here, we investigated the potential of a new drug, a more stable chemical variant of Dendrogenin B (DX243) that is predicted to display a protective function on neurite outgrowth, rather than on cell survival.MethodologyIn the rat animal model, DX243 was tested on hearing thresholds, cortical local field potentials (LFP), auditory steady-state responses (ASSR), auditory brainstem responses (ABR), growth function of notched-noise stimuli, inner hair cell (IHC) ribbon numbers, and multi-click pulse responses (MCP) before and after auditory trauma (AT).ResultsNo auditory evoked LFP response changes were seen in the prefrontal cortex, visual cortex, or hippocampus. In contrast, a permanent decline of auditory evoked LFP amplitudes in the auditory cortex (AC) was measured 2 weeks after AT. Daily injection of DX243 for 2 weeks prevented the AT-induced decline in LFP activity, a protective effect that continued for 6 weeks following the final injection. Through a protective effect of DX243 on a trauma-induced decline of LFP in response to amplitude-modulated tones >80 Hz, a subcortical origin of the drug-effect was suggested. DX243 showed no effect on hearing sensitivity and did not affect subcortical processing of sound features that depend on phase-locking at the stimulus onset (e.g., near-threshold ASSR responses, close-to-threshold ABR growth functions, or spontaneous cortical LFP responses). However, with the same dose-response dependency as shown for cortical LFP effects, DX243 significantly protected from AT-induced decreases in ABR growth functions for loud sound stimuli and in background noise, protected from AT-induced loss of IHC ribbons and AT-induced decline of fast ABRs with decreasing time intervals.ConclusionThese findings suggest DX243 as a novel neuroprotective drug, that specifically protects auditory fibers contributing to the coding of the temporal envelope and detection of tones in masking noise, tasks of our auditory senses, both of which, if they fail, lead to age-related speech-in-noise comprehension deficits.